2009
DOI: 10.1111/j.1365-2095.2008.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary administration of probiotics on growth and intestine functionality of juvenile Senegalese sole (Solea senegalensis, Kaup 1858)

Abstract: The effects of the dietary administration of two bacterial probiotic strains (Ppd11 and Pdp13) from the Alteromonadaceae family for 60 days, were assessed by measuring growth and feed efficiency, activities of leucine aminopeptidase and alkaline phosphatase and structural changes in the intestine of juvenile Senegalese sole. In addition, the profile of intestinal microbiota was studied by Denaturing Gradient Gel Electrophoresis. Growth and nutrient utilization were significantly higher in fish receiving probio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(70 citation statements)
references
References 43 publications
4
62
3
1
Order By: Relevance
“…Contrary to the present results, dietary supplementation with Pediococcus acidilactici for 32 days significantly reduced the microbial diversity in the intestine of red tilapia (Oreochromis niloticus), while improved the survival and nonspecific immune response (Ferguson et al 2010). Interestingly, several studies have demonstrated that dietary administration of probiotics exerted no apparent effect on the gut microbiota of fish (Saenz de Rodriganez et al 2009;Merrifield et al 2010d;Sun et al 2011a;Yang et al 2011b). Therefore, different probiotic strains may exert different impact on the gut microbiota of fish.…”
Section: Discussioncontrasting
confidence: 83%
“…Contrary to the present results, dietary supplementation with Pediococcus acidilactici for 32 days significantly reduced the microbial diversity in the intestine of red tilapia (Oreochromis niloticus), while improved the survival and nonspecific immune response (Ferguson et al 2010). Interestingly, several studies have demonstrated that dietary administration of probiotics exerted no apparent effect on the gut microbiota of fish (Saenz de Rodriganez et al 2009;Merrifield et al 2010d;Sun et al 2011a;Yang et al 2011b). Therefore, different probiotic strains may exert different impact on the gut microbiota of fish.…”
Section: Discussioncontrasting
confidence: 83%
“…There are, however, some common mechanisms of action that have been reported for the majority of probiotic strains. Probiotics help in feed conversion efficiency and live weight gain [27,28] and confer protection against pathogens by competitive exclusion for adhesion sites [29,30], production of organic acids (formic acid, acetic acid, lactic acid), hydrogen peroxide and several other compounds such as antibiotics, bacteriocins, siderophores, lysozyme [31e35] and also modulate physiological and immunological responses in fish [36,37].…”
Section: Probiotics In Fish Culturementioning
confidence: 99%
“…One of the principal objectives of this review is to focus on the interaction between Mediterranean teleosts and probiotics from an immunological viewpoint looking at their use and potential application at the larval and adult stages. Beyond these immunological parameters however, probiotic applications in Mediterranean teleosts have also been demonstrated to improve growth performance, feed utilisation, digestive enzyme activity, antioxidant enzyme activity, gene expression, disease resistance, larval survival, gut morphology, alter the gut microbiota and mediate stress responses [56e58, 63,66,78,79]. Perhaps slightly overlooked, as probiotics are often mistakenly viewed as dietary ingredients as opposed to live microbes artificially implanted in the gut of fish, is to understand how probiotic cells interact with endogenous gut microbes and if they colonise the GI tract.…”
Section: Probiotic Applications For Mediterranean Speciesmentioning
confidence: 99%